Point‐of‐care PT and aPTT in patients with suspected deficiencies of coagulation factors. (7th July 2016) - Niederdöckl, J.; Dempfle, C.‐E.; Schönherr, H.‐R.; Bartsch, A.; Miles, G.; Laggner, A.; Pathil, A.
Summary: Introduction: There are several clinical settings and patient conditions especially in intensive care units, emergency departments, and operating theaters, where the coagulation status of a patient must be known immediately and point‐of‐care (POC) systems are beneficial due to low time to result. Methods: This noninterventional, single‐blinded, multicenter study with prospectively collected whole blood samples was performed to evaluate the diagnostic accuracy of the CoaguChek PT Test (POC PT) and CoaguChek aPTT Test (POC aPTT) compared to standard laboratory testing in patients with suspected deficiencies of coagulation factors. Results: In total, 390 subjects were included. Both POC PT and POC aPTT showed concordance with the laboratory PT and aPTT. Lot‐to‐lot variation was below 2% both for POC PT and for POC aPTT. The mean relative difference of capillary blood compared to venous blood was 0.2 % with POC PT and 8.4% with POC aPTT. The coefficients of variation for repeatability of POC PT using whole blood were found to be between 2% and 3.6%. Conclusion: Our findings suggest reliable quantitative results with this POC system to support on‐site decision‐making for patients with suspected deficiencies of coagulation factors in acute and intensive care.